A sociographic study of student groups - Forman, Lionel (Department of Sociology, 2016)
The present investigation is one of social groups and not of the individuals who make up the groups. The aim was to obtain information about a fairly large number of groups and to attempt to express differences between groups, in quantitative terms. The small, selective sample of students are of no interest as biohoms, or even as socii. The subject of the investigation is the groups which the students list. The students are of interest only as a background to the work - to make it clear that the sample of groups which has been collected is a very selective one. This was not the original intention. The investigation was originally intended to be a study of the nature of the social groups to which social science students belong, as related to their attitudes and personal relationships within the social science class. This was to have been divided into three sections: 1. The collection of information on the social groups. 2. The collection of information on the attitudes of the students and their personal relationships. 3. The correlation of the results. The questionnaire which was drawn up for section 1, was prepared with the second part of the investigation in mind. When, however, a preliminary analysis of the results of this questionnaire was made, it was seen that a great deal of information on the social groups had been collected. The suggestion was made by Professor Batson that it might be profitable to concentrate on the analysis of these results, rather than to proceed with the second part of the investigation.